Shear Bond Strength of an Etch-and-rinse Adhesive to Er:YAG Laser- and/or Phosphoric Acid-treated Dentin - Abdolrahim Davari; Mostafa Sadeghi; Hamid Bakhshi (Tabriz University of Medical Sciences, 2013)
Background and aims. Er:YAG laser irradiation has been claimed to improve the adhesive properties of dentin; therefore, it has been proposed as an alternative to acid etching. The aim of this in vitro study was to investigate the shear bond strength of an etch-and-rinse adhesive system to dentin surfaces following Er:YAG laser and/or phosphoric acid etching. Materials and methods. The roots of 75 sound maxillary premolars were sectioned below the CEJ and the crowns were embedded in auto-polymerizing acrylic resin with the buccal surfaces facing up. The buccal surfaces were ground using a diamond bur and polished until the dentin was exposed; the samples were randomly divided into five groups (n=15) according to the surface treatment: (1) acid etching; (2) laser etching; (3) laser etching followed by acid etching; (4) acid etching followed by laser etching and (5) no acid etching and no laser etching (control group). Composite resin rods (Point 4, Kerr Co) were bonded to treated dentin surfaces with an etch-and-rise adhesive system (Optibond FL, Kerr Co) and light-cured. After storage for two weeks at 37°C and 100% humidity and then thermocycling, bond strength was measured with a Zwick Universal Testing Machine at a crosshead speed of 1 mm/min. Data was analyzed using parametric and non-parametric tests (P<0.05). Results. Mean shear bond strength for acid etching (20.1±1.8 MPa) and acid+laser (15.6±3.5 MPa) groups were significantly higher than those for laser+acid (15.6±3.5 MPa), laser etching (14.1±3.4 MPa) and control (8.1±2.1 MPa) groups. However, there were no significant differences between acid etching and acid+laser groups, and between laser+acid and laser groups. Conclusion. When the cavity is prepared by bur, it is not necessary to etch the dentin surface by Er:YAG laser following acid etching and acid etching after laser etching.